Physical-chemical characterization and wet milling yield of four maize hybrids - Mussolini, Renata C. [UNESP]; Lopes Filho, José Francisco [UNESP]; Duarte, Aildson P. (FapUNIFESP (SciELO), 2014)
The influence of physical-chemical characteristics of maize grains and lactic acid concentrations on byproduct yields, generated by conventional wet milling, was studied during steeping, for four maize hybrids and two lactic acid concentrations (0.55 and 1.00%). For physical-chemical characterization, grain dimensions (length, thickness, and width) were determined, as well as mass of 100 grains, percentage of floating grains, volumetric mass, and centesimal composition. Statistical differences were found for percentage of floating grains (2.33 to 24.67%), volumetric mass (0.814 to 0.850 kg.L-1), mass of 100 grains (0.033 to 0.037 kg), water content (11.86 to 12.20%), proteins (8.21 to 9.06%), lipids (3.00 to 4.77%), and ashes (1.07 to 1.26%). There were no relationships of wet milling yields with maize appearance and physical-chemical characteristics. The addition of 1.00% lactic acid did not statistically improve byproduct yields; however, it favored separation of the grain components.

Para verificar a influência da aparência e as características físico-químicas do grão de milho e da concentração de ácido lático durante a maceração nos rendimentos de subprodutos da moagem úmida convencional, quatro híbridos de milho foram caracterizados e macerados em duas concentrações de ácido lático (0,55% e 1,00%). Para a caracterização físico-química dos grãos, foram determinadas suas dimensões (comprimento, espessura e largura), massa de cem grãos, porcentagem de grãos boiantes, massa volumétrica e análise da composição centesimal. Diferenciaram-se estatisticamente entre os grãos a porcentagem de grãos boiantes (2,33% a 24,67%), massa volumétrica (0,810 kg L-1 a 0,850 kg L-1), massa de cem grãos (0,033 kg a 0,037 kg), teor de água (11,86% a 12,20%), proteínas (8,21% a 9,06%), lipídeos (3,00% a 4,77%) e cinzas (1,07% a 1,26%). Verificou-se que não há relação entre a aparência ou a composição química dos grãos com seus rendimentos de subprodutos na moagem úmida. A adição de 1,00% de ácido lático não proporcionou, estatisticamente, melhores rendimentos de subprodutos, entretanto facilitou a separação dos componentes do grão.
Caracterização físico-química e rendimento da moagem úmida de quatro híbridos de milho
Keywords: Zea mays L.; propriedades físico-químicas; recuperação de amido; maceração; Zea mays L.; physical-chemical properties; starch recovery; steeping